2008
DOI: 10.1016/j.mod.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Viperous fangs: Development and evolution of the venom canal

Abstract: Fangs are specialised long teeth that contain either a superficial groove (Gila monster, Beaded lizard, some colubrid snakes), along which the venom runs, or an enclosed canal (viperid, elapid and atractaspid), down which the venom flows inside the tooth. The fangs of viperid snakes are the most effective venom-delivery structures among vertebrates and have been the focus of scientific interests for more than 200 years. Despite this interest the questions of how the canal at the centre of the fang forms remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…At birth 3-4 developing generations of teeth are found linked to the dental lamina, making a developmental series ready to replace the functional tooth. In fanged snakes this series of replacement teeth is even longer, with approximately eight teeth ready to place the fangs [49], similar to the number of replacement teeth observed in the chondrichthyans. In the crocodilia, only one developing replacement tooth is observed behind the functional tooth, and together with the dental lamina they form a family unit [46].…”
Section: Reptilessupporting
confidence: 52%
“…At birth 3-4 developing generations of teeth are found linked to the dental lamina, making a developmental series ready to replace the functional tooth. In fanged snakes this series of replacement teeth is even longer, with approximately eight teeth ready to place the fangs [49], similar to the number of replacement teeth observed in the chondrichthyans. In the crocodilia, only one developing replacement tooth is observed behind the functional tooth, and together with the dental lamina they form a family unit [46].…”
Section: Reptilessupporting
confidence: 52%
“…Most elaborated fangs have an enclosed canal, and Zahradnicek et al (Zahradnicek et al, 2008) have shown that this canal forms during development by proliferation-induced invagination of the epithelium, resulting in a groove that eventually closes off from the surface. The molecular regulation of this epithelial folding seen in fangs, however, remains unknown.…”
Section: Tooth Shape Development In Reptilesmentioning
confidence: 99%
“…This canal communicates with the outside through two orifices, proximal oval foramen and distal oval foramen (Zahradnicek et al 2008). Venom passes from the venom gland into the fangs entering the proximal oval foramen and is delivered through the distal foramen into the prey (Jackson 2002;Zahradnicek et al 2008). The triangular maxilla contacts dorsally the prefrontal bone, caudally the ectopterygoid bone and cranially the septomaxilla.…”
Section: Venomous Snakes Odontogenic Abscess Stomatitismentioning
confidence: 99%
“…Fangs in vipers (Viperinae) and pit vipers (Crotalinae) are highly modified fangs (solenoglyphous), have a smooth surface and host the venom canal (VC). This canal communicates with the outside through two orifices, proximal oval foramen and distal oval foramen (Zahradnicek et al 2008). Venom passes from the venom gland into the fangs entering the proximal oval foramen and is delivered through the distal foramen into the prey (Jackson 2002;Zahradnicek et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation